2016
DOI: 10.20473/j.djmkg.v49.i4.p217-222
|View full text |Cite
|
Sign up to set email alerts
|

The effect of peer support education on dental caries prevention behavior in school age children at age 10-11 years old

Abstract: Background: Dental caries is an infectious disease and it is preceded by a progressive demineralization in hard tissue surface of the crown. Dental caries is one of the most common diseases that experienced by school-age children. Health education on the prevention of dental caries and peer support education method can improve the behavior of caries prevention. Purpose: This study aimed to determine the effect of peer support education on dental caries prevention behavior in children of school age. Method: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 3 publications
1
15
0
2
Order By: Relevance
“…Furthermore, the use of dental floss almost doubled and this was statistically significant. Consistent with our findings, other researchers have found that peer-led approaches are more influential than the adult-led approaches in enhancing oral health-related behavior [ 47 , 48 ], [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the use of dental floss almost doubled and this was statistically significant. Consistent with our findings, other researchers have found that peer-led approaches are more influential than the adult-led approaches in enhancing oral health-related behavior [ 47 , 48 ], [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 92%
“…Although the OHIS and PHP index are usually used to measure oral hygiene, the PHP index is far more sensitive. [ 17 ] The debris in OHIS measurements can easily be lost by chewing fibrous food or gargling hard without having to brush the teeth. [ 18 ] In contrast, the plaque in PHP measurements can only be removed by brushing teeth routinely with the correct technique.…”
Section: Discussionmentioning
confidence: 99%
“…The studies took place in a variety of contexts, including Pakistan (19,20), India (21), Indonesia (22), Iran (23,24), Mexico (25), Hong Kong (26), Canada (27), and Finland (28).…”
Section: Study Characteristicsmentioning
confidence: 99%